A Clinicoepidemiological Study of Melanoma in Young Patients (20 Years of Age or Less) in Alberta, Canada, From 1992 to 2011. Issue 2 (March 2021) - AlZahrani, Fatmah; Kuzel, Paul; Metelitsa, Andrei; Smylie, Michael; Dover, Douglas; Fiorillo, Loretta
The epidemiological trends of malignant melanoma have been well described in the literature. However, there remains a paucity of population-based studies assessing melanoma epidemiology in our younger patients (20 years of age or less). Other studies indicate that melanoma incidence has risen in pediatric populations over the last several decades and that these tumors may display different clinical characteristics from those arising in adult populations. We conducted a retrospective, population-based analysis of all incident cases of melanoma occurring in young patients aged ≤20 years in Alberta from 1992 to 2011. Information, including patient age, sex, anatomical location, date of diagnosis, histological subtype (if available), level of invasion, and date of death (if applicable), was obtained from the Alberta Cancer Registry. All cases occurring during a 10-year period from 1993 to 2011 have been reviewed. A total of 71 cases were diagnosed during this time (63% female and 37% male). Age range was 0-20 years (mean of 17.5 years). Truncal melanomas made up 36% of cases, while 28% occurred on the lower limbs, 17% on the upper limbs, and 18% in the head and neck region. Average Breslow thickness was 1.97 mm; 67% of tumors were less than 1 mm thick. Unfortunately, 8 of 71 patients died from their disease. Overall, the incidence of melanoma in patients aged ≤20 years appeared to decrease in Alberta in the past 20 years; however, there has been an increase in the thickness of melanoma at diagnosis, which needs to be addressed.